Dynamic batch rekeying scheme using Multiple Logical key trees for secure multicast communication - Senan, Shayma; Hashim, AishaHassan A.; Othman, Raihan; Messikh, Azeddine; Zeki, Akram M. (2015 International Conference on Computing, Control, Networking, Electronics and Embedded Systems Engineering (ICCNEEE), 2015)
A group key management has an important role in multicast security in order to achieve data integrity and confidentiality. The session key is a common secret key for a group of users in key trees that is shared securely and efficiently among them. It is used to encrypt other session keys and transmitted data in order to protect group communication. This paper proposed a new key management protocol using Multiple Logical key trees for dynamic groups. To minimize the communication overhead of rekeying process, a one-way key derivation are integrated with multiple logical key trees. New keys created by the server of the key tree are not sent to the members who are able to derive their own keys. As a result each rekeying process requires less number of encrypted keys sent within the group tree. The performance analysis of the proposed scheme shows that it has less communication cost than the other compared protocols.